Pemeriksaan Setempat Oleh Hakim Dalam Perkara Pidana - Desmon, Andi; Angelia, Rina Rahma Ornella; Erwin, Rahmi (JURNAL USM LAW REVIEW, 2023)
Research on local examinations by judges in criminal cases aims to find out and obtain a comprehensive picture regarding local examinations by judges in criminal cases. This research is important to do, because in the development of judicial practice in Indonesia, local examinations conducted by judges are not only carried out on civil cases, but are also practiced in the settlement of criminal cases. Even though the Criminal Procedure Code does not regulate local examinations in the verification process carried out by judges in criminal cases. Implicitly the Criminal Procedure Code only regulates reconstruction or reconstruction activities carried out by investigation at the investigative stage. This research is a legal research using bid-invitation approach and case approach. Based on the results of the research, it was concluded that local examinations by judges in criminal cases are the judge's discretion to clarify and validate a piece of evidence to find legal facts, which aims to increase the judge's confidence in giving a decision on a criminal case being examined. The discretionary authority possessed by judges in carrying out local examinations in criminal cases is facultative, meaning that it is not a priori binding and is only complementary, the implementation of which depends on the judge's judgment. Legally, a local examination by a judge in a criminal case is part of the evidence in the judicial process. Therefore theoretically included in the law of evidence. Penelitian tentang pemeriksaan setempat oleh Hakim dalam perkara pidana bertujuan untuk mengetahui dan memperoleh suatu gambaran yang komprehensif terkait pemeriksaan setempat oleh Hakim dalam perkara pidana. Penelitian ini penting dilakukan, karena dalam perkembangan praktek peradilan di Indonesia, pemeriksaan setempat yang dilakukan oleh Hakim tidak hanya dilakukan terhadap perkara perdata saja, namun juga dipraktikkan dalam penyelesaian perkara pidana. Padahal KUHAP tidak mengatur tentang pemeriksaan setempat dalam proses pembuktian yang dilakukan oleh Hakim dalam perkara pidana. Secara implisit KUHAP hanya mengatur kegiatan rekonstruksi atau reka ulang yang dilakukan oleh penyidik pada tahap penyidikan. Penelitian ini merupakan penelitian hukum yang menggunakan metode pendekatan perundang-undangan dan pendekatan kasus. Berdasarkan hasil penelitian, diperoleh kesimpulan bahwa pemeriksaan setempat oleh Hakim dalam perkara pidana merupakan diskresi Hakim untuk mengklarifikasi dan menvalidasi suatu alat bukti guna menemukan fakta hukum, yang bertujuan untuk menambah keyakinan hakim dalam memberikan putusan terhadap perkara pidana yang sedang diperiksa. Kewenangan diskresi yang dimiliki oleh hakim dalam melakukan pemeriksaan setempat dalam perkara pidana bersifat fakultatif, artinya tidak secara apriori mengikat dan hanya bersifat sebagai pelengkap, yang pelaksanaannya tergantung dari penilaian Hakim. Secara hukum, pemeriksaan setempat oleh Hakim dalam perkara pidana merupakan bagian dari pembuktian dalam proses persidangan. Karenanya secara teoretis masuk dalam hukum pembuktian.Diskresi; Pembuktian; Pemeriksaan Setempat.  .
Keywords: Discretion; Evidence; Local Examination; Setempat; Pembuktian; Diskresi